Prosiding Seminar Nasional Fisika (E-Journal) Snf2017 Unj 2017
DOI: 10.21009/03.snf2017.02.epa.12
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Citra Digital Untuk Sampel Batuan Menggunakan Micro-Ct Scanner Skyscan 1173

Abstract: AbstrakAnalisis citra digital telah dilakukan pada sampel batuan hasil pemindaian menggunakan Micro-CT Scanner Bruker Skyscan 1173. Analisis dilakukan secara kualitatif dan kuantitatif untuk mengetahui karakteristik dari citra sampel batuan. Sampel digital batuan yang dihasilkan dari proses pemindaian tersebut berukuran 380×380×380 piksel. Analisis kualitatif dilakukan dengan menggunakan perangkat lunak CTAn (2D) dan CTVox (3D). Analisis kuantitatif dilakukan dengan perhitungan ukuran pori, porositas terbuka, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In this study, bone substitution material from HAGP and BHA scaffold was used as a comparison. The morphology of both HAGP and BHA scaffold sizes along with alveolar bone density was analysed using Micro-CT. 13 The Micro-CT analysis results showed that the morphology of HAGP scaffold size was unequal with that of the BHA scaffold size. The HAGP scaffold was approximately 500 µm, while the BHA scaffold was approximately 250 µm.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, bone substitution material from HAGP and BHA scaffold was used as a comparison. The morphology of both HAGP and BHA scaffold sizes along with alveolar bone density was analysed using Micro-CT. 13 The Micro-CT analysis results showed that the morphology of HAGP scaffold size was unequal with that of the BHA scaffold size. The HAGP scaffold was approximately 500 µm, while the BHA scaffold was approximately 250 µm.…”
Section: Discussionmentioning
confidence: 98%